Political Career Of Rahmah El Yunusiyyah 1950-1969: Karir Politik Rahmah El Yunusiyyah 1950-1968 - Farhan Metisa Marda; Buchari Nurdin; Liza Husnita (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This study discusses the work of Rahmah El Yunusiyyah in the field of politics, therefore the purpose of this research is to describe the background of Rahmah El Yunusiyyah joining the political field, the work of Rahmah El Yunusiyyah in the field of politics, and how politics influences the education of Diniyyah Puteri. This research method is Library Research using a philosophical approach and a historical approach. The results of this study are to explain how Rahmah El Yunusiyyah's background joined the political field.